GÊNEROS DIGITAIS NO ENSINO DE LÍNGUA PORTUGUESA: ANÁLISE DE MATERIAL APOSTILADO - Cacilho, Marco Antonio (2016)
The aim of this study is to contribute to the analysis of Portuguese language handout, driven by the need of improving the textual genre teaching, in terms of digital means. Thus, the main aim is to analyze which classes provide digital genres as handout teaching objects, geared to pupils of high school first year. The specific aims are: I) to undertake a mapping of which are the textual genres of digital means approached in such classes; II) to comprehend the global plan of classes that provide the digital genres as teaching objects, through their macrostructure; III) to analyze class activities which provide digital genres as teaching objects, by means of language capacities. In order to conduct this research, we used qualitative and quantitative approaches, and documentary research. We emphasize that the material chosen offers three students` books: 1) the text-book, which presents the theory corresponding to the scheduling showed, developed into chapters, approaching application models and answered activities; 2) the handout-book used between classes, which structure the class presentation into topics, synopses, summaries, activities to be worked at classes, and minimal and complementary tasks that lead the pupil to check the exercise-book; 3) the exercise-book, which contains every single exercise suggested in the minimal and complementary tasks, and also brings answers and solves each of them. We keep in mind the importance of this analysis to get a broader vision about the configuration presented, and the way that tasks and texts are distributed in one chapter that envisage digital means. We highlight that the approached theme is concentrated into the material used by high school first years, and it is part of educational system proposed planning. We attach importance to the analysis, for it leads to a thought about underlying teaching purposes into the didactic material. This study is anchored by sociodiscursive interactionism and text genre (BRONCKART, 2012; SCHNEUWLY, 2004) theoretical frameworks, by language capacities and macrostructure concepts (DOLZ; SCHNEUWLY, 2004; DOLZ; TOULOU, 2008), as well digital genre (XAVIER, 2005; MARCUSCHI, 2008) and handout concepts (PIERONI, 1998; BUNZEN, 2001; AMORIM, 2008; SILVA, 2008). The results show that the handout studied does not consider textual genres from digital means in a satisfactory manner. Through texts and activities analyzed, we observed that none of them are in fact a copy of addressed genre, what prevents the pupil to operationalize technological resources from worldwide, and, therefore, it prevents the contact with other ways of reading and writing. In terms of macrostructure analysis, we see it as an important resource which allows us a comprehensive view of objects that must be taught. Concerning to language capacities, we noticed that most of activities bring them to bear, indirectly, due to fictitious and superficial theme`s nature. At that, to reach the goal of teaching digital genres, it is necessary to reshape the handout used by high school first year pupils.